Decompositions of multicrowns into paths and stars - Lin, Jenq-Jong (Utilitas Mathematica, 2019)
For graphs Fy G and H, a (GtH)-decomposition of F is a partition of the edge set of F into copies of G and copies of H with at least one copy of G and at least one copy of H. In this paper, we establish necessary and sufficient conditions for decomposing the multicrown into fc-paths and/c-stars. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.